2019
DOI: 10.1136/lupus-2019-000344
|View full text |Cite|
|
Sign up to set email alerts
|

Population-based prevalence and incidence estimates of primary discoid lupus erythematosus from the Manhattan Lupus Surveillance Program

Abstract: ObjectiveEpidemiological data for primary discoid lupus erythematosus (pDLE) remain limited, particularly for racial/ethnic populations in the USA. The Manhattan Lupus Surveillance Program (MLSP) is a population-based retrospective registry of cases with SLE and related diseases including pDLE in Manhattan and was used to provide estimates of the prevalence and incidence of pDLE across major racial/ethnic populations.MethodsMLSP cases were identified from rheumatologists, hospitals and population databases. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…Limitations of this study include its single-centre design and small sample size. However, the racial diversity of the UTSW CLE cohort is consistent with other epidemiological studies of DLE 12 13. Further multicentre studies are needed to confirm our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Limitations of this study include its single-centre design and small sample size. However, the racial diversity of the UTSW CLE cohort is consistent with other epidemiological studies of DLE 12 13. Further multicentre studies are needed to confirm our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Sixth, our analyses did not include other forms of lupus, such as "early" or "incomplete" lupus, drug-induced lupus, or primary cutaneous lupus (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…1 Population-based studies have found that the incidence rate of CLE is approximately 4Á0-4Á3 per 100 000 1 and that it disproportionately affects females and African Americans. [2][3][4][5][6] CLE is traditionally divided into acute, subacute and chronic CLE (ACLE, SCLE and CCLE), based on disease duration. 7 CCLE has many subtypes, including discoid LE (DLE), LE tumidus and lupus panniculitis.…”
Section: Discussionmentioning
confidence: 99%